An Analytical Study of the Impact of the war on Syria on Pharmaceutical production - أحمد أديب أحمد; عمر محمود نبع (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The aim of the research is to study the impact of the war on Syria in the reality of pharmaceutical production, which represents a range of indicators, most notably the number of pharmaceutical varieties, the number of laboratories, and the number of countries to which syrian medicine is exported, the coverage rate, and prices. The study found that the indicators of pharmaceutical production were greatly affected by the war in Syria, where it was noted that the decrease in the number of countries to which syrian medicine is exported and its types is associated with the crazy rise in domestic prices due to exchange rate changes and sanctions, as well as the rate of massive inflation, but on the other hand, because of sanctions and the cessation of export movement, the Syrian market has been covered by increasing types of medicines.